Cattle Health Monitoring System Using Arduino and IOT - Galande Sonali. A; Koyate Aishwarya N.; More Bhagyashri. S.; Prof. Gajaphode P. K. (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Now a day’s human cannot imagine their life without technology. Surrounding us diverse technologies are helping people to live their lifestyles with more luxury. The era has modified and developed many projects such as Advanced Cattle health Monitoring System using Arduino and IOT. In the Wireless Sensor Based cattle health monitoring system, critical parameters affecting cattle health which includes body temperature, humidity,and heartbeat,are continuously monitored. In this framework, Arduino UNO microcontroller is utilized to sense the various activities of animals like body temperature,humidity and heartbeat. ESP8266 Wi-Fi module is used as transceiver. The thingspeak app is used to display the graph.